Mobile Information System Pendataan Hasil Pengolahan Biji Timah Dengan Alat Meja Goyang Pada PT Timah Tbk - Anisah Anisah; Herfani Tri Nurpebri; Sarwindah .; Yurindra . (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2021)
Abstract— The high demand for tin mining commodities has pushed the development of mining product processing technology quite significantly. However, the more difficult it is to obtain available reserves and the lower the processed Tin content, the lower the selling value. One of the tools that can be used to get good quality tin with fine grains according to its level is a rocking table. Currently, the processing of data from the processing of Tin ore using a rocking table has not been carried out optimally. This situation causes the monitoring system and optimization of the use of the rocking table to not be implemented properly. The formulation of the  problme is using a mobile-based data collection system . So that the data obtained can be used as the basis for optimizing the use of the existing rocking table in each mining unit as well as increasing the ease of access to recheck on land production, especially from processing rocking table tools. For the system development model using a waterfall and the Database Management System (DBMS) used is using a SQLite database. Based on the test results, the system provides convenience in monitoring the use of the rocking table, so that tool optimization is achieved